Azacitidine as salvage therapy for relapsed acute myeloid leukemia/myelodysplastic syndrome after allogeneic hematopoietic stem cell transplantation. Issue 3 (24th April 2019) - Ozawa, Takayuki; Fuji, Shigeo; Kawashima, Ichiro; Sueki, Yuki; Hagihara, Masao; Handa, Naoko; Ito, Reiko; Yamashita, Tomoko; Kikuchi, Yuji; Ohwada, Akira; Matsuura, Yasuhiro; Yoshifuji, Kota; et al.
Abstract: Objective: There are no established salvage therapies for relapsed myeloid malignancies after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Azacitidine (AZA) has been reported as a promising treatment in such cases. Methods: We conducted a retrospective analysis of patients at our institution who received AZA for relapse after allo‐HSCT between 2014 and 2015. Results: Twenty‐two patients received AZA as salvage therapy; 19 had acute myeloid leukemia and 3 had myelodysplastic syndrome. The median number of AZA cycles was 2 (range, 1‐12). Seventy‐seven percent of patients received AZA at a dose of 75 mg/m 2 for either 5 or 7 days. The median interval between each AZA administration was 32 days (20‐63 days). Donor lymphocyte infusion (DLI) was administered in 5 patients. The median follow‐up period after AZA therapy was 360 days (range, 63‐805). The overall response rate was 15% in patients with non‐hematological CR (Non‐HCR) or hematological relapse (H‐Rel) and 56% in patients with molecular relapse (M‐Rel). The 1‐year overall survival (OS) rates in patients with Non‐HCR/H‐Rel and M‐Rel were 37.3% and 74.1%, respectively ( P  = 0.30). Patients who received DLI had favorable OS, and those with early H‐Rel had poor OS. Grade 3‐4 infection occurred in 12 patients. Discussion: Our study suggests that AZA ± DLI is a tolerable and promising treatment in M‐Rel patients. The efficacy of AZA in H‐Rel patients is limited.